2023
DOI: 10.1002/pc.27520
|View full text |Cite
|
Sign up to set email alerts
|

Improved rheological, barrier, antibacterial, and electromagnetic interference shielding properties of graphene and graphene derivatives based linear low density polyethylene nanocomposites

Abstract: Multifunctional polymer/graphene based lightweight and flexible nanocomposite films are increasingly being utilized in the packaging, electronics, and pharmaceutical industries together. Herein, two graphene derivatives: silver nanoparticle decorated reduced graphene oxide (G‐Ag) and chemically reduced graphene oxide (rGO) prepared by wet chemical method and graphene nanoplatelets (GNP) have been incorporated into linear low density polyethylene (LLDPE) thermoplastic matrix via melt compounding method. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…An elevated concentration of GNP augments the likelihood of agglomeration formation, which hinders the molecular chains from organizing into crystal lattices, ultimately diminishing the level of crystallinity. Such reduction in percentage crystallinity of rGO-and G-Ag-loaded LLDPE nanocomposites was also reported by Das et al [62]. It is noteworthy that the incorporation of a minute quantity of graphene has been observed to enhance the water resistance characteristics of PVA [98].…”
Section: Thermal Propertiessupporting
confidence: 78%
See 4 more Smart Citations
“…An elevated concentration of GNP augments the likelihood of agglomeration formation, which hinders the molecular chains from organizing into crystal lattices, ultimately diminishing the level of crystallinity. Such reduction in percentage crystallinity of rGO-and G-Ag-loaded LLDPE nanocomposites was also reported by Das et al [62]. It is noteworthy that the incorporation of a minute quantity of graphene has been observed to enhance the water resistance characteristics of PVA [98].…”
Section: Thermal Propertiessupporting
confidence: 78%
“…The improved antibacterial characteristics of graphene and graphene derivatives containing PLC, PEG and PVDF composite films that can be utilized for food packaging are also reported in the literature. Ghosh et al investigated the antibacterial effectiveness of rGO-Ag-loaded LLDPE thermoplastic nanocomposite films against both gram-positive and gram-negative bacteria by disk diffusion method [62]. The results indicated that graphene-contained thermoplastic films exhibited very effective antibacterial activity in terms of reduction in CFU (colony-forming units) against both bacterial strains [9].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 3 more Smart Citations